Characteristics of Li-bearing pegmatite in La Vi area, Quang Ngai Province - Anh, Đào Duy; Thảo, Hoàng Thị Minh; Thuyết, Nguyễn Thị Minh (Vietnam Journal of Earth Sciences, 2014)
In order to sustainable use resource of lithium ore in La Vi area, Quang Ngai province, this research was performed using ICP-MS, AAS, thin section with light microscopy, and XRD with BGMN based on Rietveld method to carry out main characteristics of the pegmatite. Observed minerals include quartz (32%), plagioclase (51%), muscovite (10%), lepidolite (4%) and impurities including orthoclase, sphene, apatite, chlorite,... (3%). The lithium-bearing mineral is lepidolite but not spodumene or pelite. The lepidolite was characterized with quite low lithium index, which is approximately 2.5% of LiO2. Average content of lithium in the bulk sample is 4674ppm, about 0,99% LiO2. The lepidolite in La Vi area belongs to the 2M1 structure. Particle size of the lepidolite mainly ranges from 30 to 300μm with the most popular size is 70 -100μm.